Refinement of the Diatom Episome Maintenance Sequence and Improvement of Conjugation-Based DNA Delivery Methods - Diner, Rachel E.; Bielinski, Vincent A.; Dupont, Christopher L.; Allen, Andrew E.; Weyman, Philip D. (Frontiers in Bioengineering and Biotechnology, 2016)
Conjugation of episomal plasmids from bacteria to diatoms advances diatom genetic manipulation by simplifying transgene delivery and providing a stable and consistent gene expression platform. To reach its full potential, this nascent technology requires new optimized expression vectors and a deeper understanding of episome maintenance. Here we present the development of an additional diatom vector (pPtPBR1), based on the parent plasmid pBR322, to add a plasmid maintained at medium copy number in E. coli to the diatom genetic toolkit. Using this new vector, we evaluated the contribution of individual yeast DNA elements comprising the 1.4-kb tripartite CEN6-ARSH4-HIS3 sequence that enables episome maintenance in P. tricornutum. While various combinations of these individual elements enable efficient conjugation and high ex-conjugant yield in P. tricornutum, individual elements alone do not. Conjugation of episomes containing CEN6-ARSH4 and a small sequence from the low GC content 3’ end of HIS3 produced the highest number of diatom ex-conjugant colonies, resulting in a smaller and more efficient vector design. Our findings suggest that the CEN6 and ARSH4 sequences function differently in yeast and diatoms, and that low GC content regions of greater than ~500 bp are a potential indicator of a functional diatom episome maintenance sequence. Additionally, we have developed improvements to the conjugation protocol including a higher-throughput option utilizing 12-well plates, and plating methods that improve ex-conjugant yield and reduce time and materials required for the conjugation protocol. The data presented offer additional information regarding the mechanism by which the yeast-derived sequence enables diatom episome maintenance, and demonstrate options for flexible vector design.